Delimitation of the Nearctic region according to mammalian distributional patterns - Escalante, Tania (2010)
The Nearctic has been recognized as a biogeographic region since the 19th century. We analyzed distributional patterns of the mammals inhabiting North and Central America, from Alaska to Panama, to delimit the boundaries of the Nearctic region. We performed 6 optimality analyses, using a grid of 4° latitudelongitude, based on families, genera, species, and combinations of these. The analysis of the matrix with the 3 taxonomic levels yielded better results in terms of the largest number of endemics and the best delimitation of the Nearctic region. We also found 3 patterns-western, eastern, and northern-within the region that coincide partially with previous biogeographic characterizations. Although mammals seem to represent appropriate taxa to delimit this region, we conclude that a more robust delimitation might be obtained by analyzing other plant and animal taxa.